2005
DOI: 10.1101/gr.4141805
|View full text |Cite
|
Sign up to set email alerts
|

Chicken genome: Current status and future opportunities

Abstract: The chicken genome sequence is important for several reasons. First, the chicken shared a common ancestor with mammals ∼310 million years ago (Mya) at a phylogenetic distance not previously covered by other genome sequences. It therefore fills a gap in our knowledge and understanding of the evolution and conservation of genes, regulatory sequences, genomes, and karyotypes. The chicken is also a major source of protein in the world, with billions of birds used in meat and egg production each year. It is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
105
1
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 62 publications
0
105
1
16
Order By: Relevance
“…clave fue el bajo contenido de DNA repetitivo, que es de solo 11 %, comparado con lo encontrado en el genoma de los mamíferos (~50 %) (Dequéant y Pourquié, 2005;Burt, 2005;Burt et al, 2007).…”
Section: Introductionunclassified
“…clave fue el bajo contenido de DNA repetitivo, que es de solo 11 %, comparado con lo encontrado en el genoma de los mamíferos (~50 %) (Dequéant y Pourquié, 2005;Burt, 2005;Burt et al, 2007).…”
Section: Introductionunclassified
“…Although only 2.5% of the chicken genome sequence could be directly aligned to the human genome, 75% of coding and between 30 and 40% of gene regulatory regions are conserved between species. 21 This degree of homology, although not perfect, may be sufficient to be informative for cross-species comparisons of genetic loci.…”
Section: Introductionmentioning
confidence: 99%
“…Those genes have been considered a common characteristic of vertebrates in general (8). During the evolution of the Aves, a number of gene families were lost from the genome, responsible for traits such as: vomeronasal receptors, casein milk proteins, proteins present in saliva and enamel proteins.…”
mentioning
confidence: 99%
“…Conducted analyses showed that the total length of the sequence of the chicken genome is more than a billion nucleotides that encode about 15 500 genes (number of genes verified by Ensembl) (28). It was found that the chicken genome has a relatively low content of repetitive sequences (11%) compared to mammals, which typically contain 40-50% of repetitive sequences in their genome (8). The low level of repetitive sequences results from the decreased overall size of the Avian genome in comparison to mammalian genomes, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation